2020
DOI: 10.1039/c9nr09505e
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of small molecules at hydrophobic interfaces using group effect

Abstract: Group effect allows non-tethered small molecules to form a wide variety of self-assembled structures at solid–liquid interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…A MeOH layer adsorbed on the graphite potentially interferes with this hydrophobic interaction between the peptide and the graphite. In particular, at concentrations more than 30% MeOH, the relatively strong intermolecular interactions between the MeOH molecules and graphite form a thin film of MeOH molecules with a strong network called group effect …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A MeOH layer adsorbed on the graphite potentially interferes with this hydrophobic interaction between the peptide and the graphite. In particular, at concentrations more than 30% MeOH, the relatively strong intermolecular interactions between the MeOH molecules and graphite form a thin film of MeOH molecules with a strong network called group effect …”
Section: Resultsmentioning
confidence: 99%
“…These authors have found that the alcohol molecules form a uniform molecular layer having a variety of self-assemblies depending on the alkyl chain length of the alcohol molecules (MeOH, EtOH, 1-prop, and IPA). This effect has been called the “group effect,” which depends on the interactions between the molecules forming the stable network . The layers of the alcohol molecules on the hydrophobic surfaces are stabilized by the group effect and competitively prevent the self-assembly of the peptides.…”
Section: Resultsmentioning
confidence: 99%
“…SURMOFs are well‐known model systems, based on MOF grown on alkanethiol functionalized gold surfaces [16–18] . Herein, we nanosized the MOF deposits to stimulate defect formation by manipulating the self‐assembly behavior of the thiol molecules promoting/inhibiting MOF growth on the substrates, yielding gapped, and even bifunctional surfaces of HKUST‐1 and ZIF‐8 [19–21] …”
Section: Figurementioning
confidence: 99%
“…[16][17][18] Herein, we nanosized the MOF deposits to stimulate defect formation by manipulating the self-assembly behavior of the thiol molecules promoting/inhibiting MOF growth on the substrates, yielding gapped, and even bifunctional surfaces of HKUST-1 and ZIF-8. [19][20][21] HKUST-1, an archetypical MOF, is highly hydrophilic and has low hydrothermal stability as its paddlewheel SBU hydrolyses in the presence of water vapor. [22,23] On the other hand, Zeolitic-Imidazolate Frameworks (ZIFs), such as ZIF-8, are hydrophobic and show increased hydrothermal and chemical stability.…”
mentioning
confidence: 99%
“…Hydrophobic surfaces can be developed through chemical [ 13 ], electrochemical [ 14 ], and physical surface treatments [ 15 ], thereby increasing surface roughness [ 16 ] or forming a surface coating [ 17 ]. To achieve nanoscale roughness on a hydrophobic surface, different techniques such as polymer solution evaporation [ 18 ], sol–gel coating [ 19 ], electrochemical deposition [ 20 ], photolithography [ 21 ], chemical etching [ 22 ], phase separation [ 23 ], self-assembly [ 24 ], and various spraying techniques are used [ 25 , 26 ]. However, these techniques for preparing hydrophobic surfaces are difficult and expensive.…”
Section: Introductionmentioning
confidence: 99%